Exploring the role of translators’ emotion regulation and critical thinking ability in translation performance - Cheng, Shufang (Frontiers in Psychology, 2022)
In recent years, the field of psychology has received more attention from researchers that work in the area of translation studies. This review set out to delve into the role of translation students’ critical thinking, as a construct of cognitive psychology, and emotion regulation, as a positive psychological construct, in translation performance. The positive and significant relationship between translation students’ critical thinking skill and their translation performance has been verified in the literature. Moreover, studies have revealed that emotion regulation and its regulator components, such as emotional intelligence, intuition, resilience, and professional expertise can significantly influence translation performance. This review can be beneficial for translation trainees, translation trainers, and curriculum designers to raise their awareness about the role of critical thinking and emotion regulation in translation studies.